Project Based Learning Pada Mata Kuliah Pengembangan Bahan Ajar untuk Meningkatkan Keterampilan 4C Mahasiswa : Penelitian - Isa Ansori; Tri Wahyuni Indah Permata (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
In the Teaching Materials Development course at the Culinary Arts Education Study Program, Surabaya State University, learning still focuses on product outcomes and has not yet developed students' 21st-century skills in a planned manner. As a result, critical thinking, creativity, collaboration, and communication (4C) skills have not developed optimally. This study aims to examine the effect of implementing Project-Based Learning on improving students' 4C skills. The study used a quantitative approach with a pre-experimental one-group pretest–posttest design on third-semester class D students. 4C skills data were collected through questionnaires before and after project-based learning, then analyzed using normality tests and paired sample t-tests. The results showed a statistically significant increase in 4C skills (p < 0.05), so Project-Based Learning was proven effective in supporting the development of 21st-century competencies in vocational education students